Exploring the potential connection between place capital and health capital in the post COVID-19 city - Meyrick, Kate; Newman, Peter (2023)
Great places have the potential to create enhanced health outcomes and improve quality of life. The positive connection between the built environment and the social determinants of health is well documented as is the role of the built environment in establishing place quality and sense of place. However, the relationship between the concepts of place capital and health capital is less understood and specifically the extent to which high levels of place capital confer a protective and restorative health benefit across the whole of life. COVID-19 changed our appreciation of the role that both health and place play in supporting our quality and way of life and has revealed the negative impact on wellness and wellbeing that arises when our connection to place is fractured. To contribute to the debate surrounding the post-COVID-19 city, this paper explores the intrinsic connection between place and health; it proposes a conceptual model that positions place capital as a tool for enhancing whole of life health capital at a neighbourhood scale. The Framework for measuring this place capital is created from traditional place literature and the new place context literature on the need to be inclusive, equitable and sustainable. It suggests that by building great places that are based on these measurable factors, there can be a reduction in the growth of medical spending and burden of disease over time.